Quality of life on the work of Administrative Technicians of IFPB/Campus Patos (Research, Society and Development, 2021)
Quality of Life at Work (QWL) has been gaining importance in modern organizations and public institutions since the 1990s. The aim of this study is to diagnose the perception of QWL of the Administrative Technicians (TA's) of the Campus Patos of the Federal Institute of Education, Science and Technology of Paraíba (IFPB) and describe their feelings to support the proposition of actions and improvements to their quality of life at work. This research is characterized as a case study of a quantitative, exploratory and descriptive nature. A questionnaire consisting of ten items with socio-functional aspects (Gender, Age, Job Level, Hierarchical Level, Salary Range, Schooling, Number of Dependents, Length of Service, Role and Syndical Membership) adapted from the Biopsychosocial and Organizational Model BPSO-96 from Limongi-France is applied. The results indicate that in relation to the organizational dimension, the subjects present good satisfaction rates, being the lowest in relation to the biological dimension. The overall assessment points to a regular level of satisfaction, indicating the need for progress in the area, as well as a more effective institutional policy.